The dominant metaphors of idiostyle of Yuri Klen (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article is focused on the debatable nature of the formed scientific approaches to understanding the fundamental principles of metaphor analysis, it is determined that the most profound and comprehensive can be considered an anthropological view on problem taking into account cognitive, cultural and linguistic aspects. It is stated that in modern Ukrainian linguistic the issue of functioning o metaphors in journalistic style text on the material of English language, artistic style on the material of German language are covered and a complex approach to understanding the phenomenon on the material of poetic text of Ukrainian language is presented. The issue of learning metaphorical idiosyncrasies of Ukrainian poets, separately Yuri Klen, was overlooked by researches. It is explored the metaphorical speech of Ukrainian writer Yuri Klen on the material poetry collection “Caravels. In the Footstep of the Conquistadors” as a means of presenting the individual-authorial linguistic picture of the world in the aspect of anthropocentric linguistic; it is emphasized that the metaphor is one of the main means of modeling the author’s subjective views of life and his artistic conceptualization. The binary conceptualization of the poet’s metaphorical system, types of metaphors, ways of their realization are analyzed namely: metaphors to denote the spatial continuum; metaphor to denote the temporal continuum; metaphors to denote the psychological state of human; metaphors to denote the realities of the environment, that surrounded a human. It is proved that the text of artistic work can be a complex and multi-layered metaphor. The classification of dominant types of metaphor is offered taking into accounts the ways of the morphological expression (simple): substantive metaphors, which are word combination with a noun as a core of component are formed according to the model “noun+noun”; substantive metaphors, which are phrases with noun as a core component are formed according to the model “noun+adjective”; “noun+participle” (metaphorical epithets). The types of metaphors according to the method syntactic organization of utterances (deployed metaphors) are distinguished: metaphor – simple sentence; metaphor – simple complicated sentence; metaphor – complex sentence.
Keywords: anthropological linguistics; individual-author`s linguistic picture of the world; metaphor; metaphorical conceptualization of the world